EKONOMI KREATIF DALAM METAVERSE: TINJAUAN EKSTENSIF TRANSAKSI ASET DIGITAL DAN HAK KEPEMILIKAN (MILKIYYAH) DALAM PERSPEKTIF FIKIH MUAMALAH BAGI KREATOR MUDA - Rohman Pranoto; Isrun Abdurahman; Rizaldy Alpiansyah; Miftah Wangsadanureja; Tatang Hidayat (Dirham : Journal of Islamic Economics, 2026)
The development of the virtual asset-based economy and digital transactions has sparked a new paradigm for young creators within the metaverse ecosystem. This transition from a conventional economy to the digital realm creates a gap between market practices and the normative approach of fiqh muamalah. Consequently, it demands an adjustment in interpretations regarding ownership (milkiyyah tammah), the legality of digital assets (such as game skins and NFTs), and the risks of speculation and fraud therein. This article analyzes the status of virtual objects based on their technological architecture—centralized and decentralized assets—and evaluates them through the lenses of Islamic law and contemporary regulations. The results of the analysis emphasize that centralized assets, such as game skins, are legally flawed due to the absence of absolute ownership rights and high levels of gharar. Conversely, decentralized NFT assets can be recognized as māl maknawi, provided that the underlying assets and the medium of exchange are free from maysir and riba. This paper is expected to serve as a reference for young creators to remain relevant in digital innovation without compromising ethical integrity and the protection of Maqashid Syariah.